Calcitonin gene–related peptide in migraine: from pathophysiology to treatment - Santos-Lasaosa, S.; Belvís, R.; Cuadrado, M.L.; Díaz-Insa, S.; Gago-Veiga, A.; Guerrero-Peral, A.L.; Huerta, M.; Irimia, P.; Láinez, J.M.; Latorre, G.; Leira, R.; Pascual, J.; et al. (Neurología (Barcelona, English ed. ), 2022)
It has been observed in recent years that levels of such molecules as calcitonin gene–related peptide (CGRP) and, to a lesser extent, the pituitary adenylate cyclase–activating peptide are elevated during migraine attacks and in chronic migraine, both in the cerebrospinal fluid and in the serum. Pharmacological reduction of these proteins is clinically significant, with an improvement in patients’ migraines. It therefore seems logical that one of the main lines of migraine research should be based on the role of CGRP in the pathophysiology of this entity. The Spanish Society of Neurology’s Headache Study Group decided to draft this document in order to address the evidence on such important issues as the role of CGRP in the pathophysiology of migraine and the mechanism of action of monoclonal antibodies and gepants; and to critically analyse the results of different studies and the profile of patients eligible for treatment with monoclonal antibodies, and the impact in terms of pharmacoeconomics. The clinical development of gepants, which are CGRP antagonists, for the acute treatment of migraine attacks, and CGRP ligand and receptor monoclonal antibodies offer promising results for these patients. En los últimos años se ha observado que moléculas como el péptido relacionado con el gen de la calcitonina (CGRP) y, en menor grado, el péptido activador de la adenilato-ciclasa pituitaria (PACAP) estaban elevadas durante los ataques de migraña y en la migraña crónica tanto en líquido cefalorraquídeo como en suero y que su reducción farmacológica tenía una significación clínica con una mejoría en la migraña de los pacientes. Es lógico por tanto que una de las principales líneas de investigación en migraña se base en el papel del CGRP en la fisiopatología de esta entidad. Desde el Grupo de Estudio de Cefaleas de la Sociedad Española de Neurología nos planteamos la redacción de este documento, cuyo objetivo es abordar, basándonos en la evidencia publicada, cuestiones tan importantes como el papel del CGRP en la fisiopatología de la migraña, el mecanismo de acción de los AMC y de los gepantes, el análisis crítico de los resultados de los diferentes estudios, el perfil del paciente que podría ser candidato al tratamiento con AMC y su impacto en términos de farmacoeconomía. El desarrollo clínico de los gepantes, antagonistas del CGRP, para el tratamiento agudo del ataque de migraña y de los anticuerpos monoclonales (AMC) contra ligando y contra el receptor del CGRP, ofrecen resultados esperanzadores para nuestros pacientes.